Power IMS access network evolution and integrated method - Xiande BU; Shouyong LI; IBinglin L; IANWenfeng T (Dianxin kexue)
The State Grid had decided to construct next generation switching network using IMS technology,so the existing access devices and equipments needed to be updated or formed.Four kinds of access equipment unit were introduced,which were access gateway（AG）,integrated access device（IAD）,IP PBX and SIP phone.According to the functions and usage of above 4 equipments,the method to construct the access network to update the old one was analyzed.Incorporation with application scenes of communication services,the different access methods were researched and the project solutions for SGCC was put forward to build IMS access network.